MENGURAI DIVERGENSI KONSEP PEMASARAN MELALUI PERKEMBANGAN IMPLEMENTASI - Amin Wibowo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
Among the divergence of marketing concepts there are kinds of similarity among them in many aspects : (1) the basic assumptions in defining marketing and marketing management, almost all scholars agree that terms of consumer becomes starting point in defining marketing concept. The substantive differences among the concepts accured in focusing to customers. For instance, Benneth and Cooper placed the focus on customers with minimal proportions because of their paradigm and experiences. (2) Market oriented and customer oriented have similarity in substantive manner, but in industrial marketing, the proportion of attention toward customers is very limited. Meanwhile, marketing scholars view totally to customers oriented. (3) Industrial marketing concern on institutionalized customer (or market oriented) that is not limited on marketing division, but covers top management responsibility in implementing business strategy and strategic planning. (4) in the context of marketing concept, Huston’s ideas about marketing concept is make sense whenever marketing is the behaviors that creates exchange between buyer and seller. Exchange is not in “one shot” activity.